ESRC-DFID Research for Policy and Practice: Water Security - Impact Initiative (Institute of Development Studies and The Impact Initiative, 2019)
Access to clean water is essential for life but all too often in water management, short-term gains for the few are prioritised above long-term benefits for the many. This selection of ESRC-DFID funded research explores the realities facing people for whom water insecurity is a daily threat, drawing on research focusing on Burkina Faso and Ethiopia.This includes briefs on two WLE-supported projects: "Water scarcity and emotional wellbeing among pastoralists" and "Engaging communities for sustainable water management in Burkina Faso."